Beneficial Root Endophytic Fungi Increase Growth and Quality Parameters of Sweet Basil in Heavy Metal Contaminated Soil - Sabra, Mayada; Aboulnasr, Amal; Franken, Philipp; Perreca, Erica; Wright, Louwrance Peter; Camehl, Iris (Frontiers in Plant Science, 2018)
Accumulation of heavy metals in the food chain has led to stricter environmental regulations in the past decades because of its toxicity to humans, animals and aquatic life. The interaction between contaminated soil, plants and the rhizosphere for environmental sustainability is still under research. We used two root endophytic fungi, the arbuscular mycorrhiza fungus (AMF) Rhizophagus irregularis and the beneficial endophyte Serendipita indica to test the effect on sweet basil (Ocimum basilicum) in a pot experiment with soil contaminated with lead and copper under defined greenhouse conditions. Both fungi mediate an increase in shoot and root dry weight of sweet basil plants under all conditions and decrease the amount of lead in shoots. The amount of copper was reduced by S. indica, while the AM fungus showed this effect only when soils were contaminated with both heavy metals. Furthermore, the AMF, but not the endophyte S. indica revealed a strong increasing effect on the concentrations of the essential oils linalool and eucalyptol even on contaminated soils. Hence, cultivating sweet basil with beneficial fungi under difficult environmental conditions could be of interest for industry, because quantity and quality of plants are increased while the amount of heavy metals is generally reduced.